Měření momentů setrvačnosti vozidla - Grác, David (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Tato diplomová práce se zabývá zvolením vhodné metody pro zjištění momentu setrvačnosti ke svislé, příčné a podélné ose procházející těžištěm vozidla. Pomocí speciálního mechanického stavu, zkonstruovaného na ÚADI, bylo provedeno opakované měření tělesa o známých hmotnostních parametrech v jednotlivých osách. Ze získaných dat byla následně vypočítána chyba měření. Pro porovnání výsledných hodnot byl vytvořen MBS model.

This diploma thesis is concerned with selecting the appropriate method for determining the moment of inertia to the vertical, lateral and longitudinal axis through the centre of gravity of the vehicle. Using the special mechanical device, constructed on IAE was carried out repeated measurements of known mass properties in each axis. With the aid of obtained data was calculated measurement error. To compare the resulting values was created MBS model.
Measurement of vehicle moments of inertia
Keywords: těžiště; moment setrvačnosti; perioda kmitu; simulace; Multi-body systém; centre of gravity; moment of inertia; oscillation period; simulation; Multi-body system